Językowe fascynacje Floriana Śmiei - Miodek, Jan (Słowo. Studia językoznawcze, 2020)
The aim of the article is to disscus the linguistic fascinations of Florian Śmieja, writer, poet, publicist, profesor at English and Canadian universities who spent his childhood and youth in Silesia. The author of the article analyzes the words related to the Silesia region, selected form of the poems which are lexical markers of Florian Śmieja’s Silesian origin. He discusses their structure, etymology, lexical meaning and function in the analized texts. Presented observations lead to the conclusion that the linguistic fascinations of mother tongue are constantly present in his narrative and life. One can read from them the immense longing for the Silesian land and the Silesian as a regional dialect.